Characterization of the mineralizing fluids of the Quebrada del Diablo Lower West epithermal gold deposit, Argentina - D'annunzio, María Celeste (2018)
The Gualcamayo Mining District (GMD) is located in the eastern Precordillera of Argentina. Gold mineralizationin the district is hosted by three deposits (Fig. a): Amelia Inés- Magdalena (AIM), Quebrada del Diablo (QDD) Main,and Quebrada del Diablo (QDD) Lower West.The oldest rocks of the GMD area are Late Cambrian to Early Ordovician marine platform limestones. Theserocks are overlain by Middle Ordovician shales and Upper Ordovician siliciclastic conglomerates and sandstonesdeltaic deposits. These deposits are discordantly overlain by post-glacial transgressive facies and a long-lived sequenceof paralic sedimentary facies of Carboniferous to Permian age. The Paleozoic sequence is intruded by the GualcamayoIgneous Complex, which consists of subvolcanic dacitic intrusives of Late Miocene age (~9 Ma) (Fig. a).AIM consists of veinlets and breccias with a paragenesis of pyrite, chalcopyrite, sphalerite, arsenopyrite,gold, calcite, and quartz which overprints a skarn mineralization.QDD Main is a gold deposit hosted in dissolution and collapse carbonatic breccias affected by dolomitization,silicification, and decarbonatization. The gold mineralization consists of free gold in microscopic grains spatiallyassociated to oxidized sulfides (pyrite, marcasite, As-pyrite, chalcopyrite, sphalerite, and pyrrhotite), galena,orpiment, realgar, cinnabar, calcite, quartz, gypsum, and barite.QDD Lower West is a gold deposit with an ore grade of 2.85 g/t located at ~ 600 m depth and to the westof QDD Main. The mineralization of QDD Lower West is hosted by the cement of tectonic breccias conforming anirregular body elongated in West-East direction of 500 m long, 100 to 150 m wide and ~150 m thick. Threealteration-mineralization stages were recognized in this deposit. The first stage consists of a fine-grainedintergrowth of pyrite, arsenopyrite, chalcopyrite, and sphalerite forming the cement of tectonic breccias. Thisore paragenesis is spatially associated with sparitic calcite (I) and microcrystalline aggregates of quartz (I). Pyriteand chalcopyrite of the first stage are replaced by hypogene marcasite and covellite, respectively, suggesting anincrease in φS during this mineralization stage. The second stage is formed by barren calcite veinlets (calcite II).The third stage consists of fine-grained intergrowths of calcite (III), adularia and quartz (II) in veinlets and minorhydrothermal breccias. Spatially associated with these minerals there are realgar, orpiment, calaverite, andcoloradoite.The aim of our research is to establish the physicochemical conditions and the origin of the mineralizing fluidsof the QDD Lower West gold deposit based on ore paragenesis, isotopic, LA-ICP-MS and fluid inclusion studies inorder to build a genetic model for this deposit.